Gender and Race Heterogeneity: The Impact of Increases in Students with Limited English on Native Students' Performance - Timothy M. Diette; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2013)
The influx of immigrants has shifted the ethnic composition of public schools in many states including North Carolina. Recent evidence from North Carolina suggests that increases in Limited English students' concentration have led to a slight decline in performance solely for students at the top of the achievement distribution. The heterogeneous peer effects by achievement level lead us to explore in this paper whether the increased immigration has differential effects by gender and race. Utilizing fixed effects methods that allow us to address possible endogeneity with respect to the schools' students attend, we find heterogeneous peer effects of limited English students on natives' performance in math and reading. Specifically, we find no peer effects on white females but small negative effects on males and blacks on average.
Keywords: I20; I21; J15; J24; 330; immigrants; student achievement; peer effects; education; race; gender; limited English students